Gestión de inventario del departamento de guardalmacén del GAD Municipal del cantón Ventanas - Muñoz Barragán, Verónica Liliana (2021)
This study is carried out in the decentralized autonomous government of the canton Ventanas specifically in the warehouse area where all factors related to proper inventory management are analyzed, however, events that generate conflicts in this area have been identified and significantly affect The activities and results that the stories should obtain refer to: lack of knowledge of personnel, lack of punctuality of personnel for work hours, poor handling of technological tools, delay in delivery of information, lack of monitoring of the application of legal regulations, insufficient space, lack of control of material flows and purchase planning; the same ones that specifically to the performance of the department. For this purpose, the research line of the commercial engineering career, financial, administrative, tax management, auditing and control was used and the sub-line company public and private institutions that allow to achieve the proposed objective in addition to the application of descriptive research methods , analytical and bibliographic based on a quantitative research through the use of the techniques and instruments interview questionnaire and survey questionnaire that has allowed to determine the causes and effects identified by the person in charge and the collaborators who carry out their activities on a daily basis in the department .